The Dynamic DNA Demethylation during Postnatal Neuronal Development and Neural Stem Cell Differentiation - Huikang Tao; Pei Xie; Yuhang Cao; Liqi Shu; Liping Li; Junchen Chen; Guangfeng Tian; Yingliang Zhuang; Qiang Shu; Xuekun Li (Stem Cells International)
Background. DNA demethylation, the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC), plays important roles in diverse biological processes and multiple diseases by regulating gene expression. Methods. In this study, utilizing DNA dot blot, immunofluorescence staining, and qRT-PCR, we studied the expression pattern of Tets, the enzymes governing DNA demethylation, and the levels of 5hmC, 5fC, and 5caC during the postnatal neuronal development of mice. Results. It was found that 5hmC, 5fC, and 5caC were highly enriched in multiple brain regions and aNSCs and displayed temporal and spatial patterns during postnatal neuronal development and the differentiation of aNSCs. Consistently, the expression of Tets also exhibited temporal and spatial patterns. Conclusion. DNA demethylation displayed dynamic features during postnatal neuronal development and the differentiation of aNSCs of mice, which could contribute to appropriate gene expression.